On the Minimal Annulus of Triangles and Parallelograms - Vassallo, Salvatore (Armenian Journal of Mathematics, 2023)
Sharp upper and lower bounds for the isoperimetric deficit of triangles or parallelograms with the minimal annulus of radii R and r are given.